Mechanisms of Integration of Referential and Performative Functions of the Actor's Vocal and Somatic Actions the theatrical (Journal of the College of Basic Education, 2023)
(Simulation) was born from the womb of life, and primitive man revealed, through it, some of theFormulas for expressing his needs and instincts, such as (fear, hunger, joy…..etc), with the effect ofHis interaction and struggle with nature, represented by means embodied in gestures and signs takenLater, social formulas such as the dances practiced by man in his religious ritualsand social, and what it includes of local and transitional movements and gestures.However, it did not deviate from its life function, as "the primitive dances of the first manIt included the liveliness of the dance without having the character of art” (1). And with the development of human lifeAnd the complexity of his material and moral needs, his expressive means developed, and it became for vocal expressionHis importance in promoting those gestures and motor signals, and thus occupied his vocal meansMovement had its place within his primitive ritual practices, which later developed into manifestations of(semi-play), and then to an independent form that was later called (Dharma Art), which embodiedTurn clearly in (the ancient Greek civilization).The actor's work crystallized as a functional (utilitarian) necessity associated with worship and ritual practice.religious, and artistic aspects that followed tasteful aspects associated with pleasure, and accordingly (the actor) acquiredtheatrical) his importance from the formation of the theatrical phenomenon, and that of his presence and interaction with it inLimits of regulating his own abilities and capabilities (vocal and physical) in order to fulfill the requirements of the dramatic situation.And what it requires of an attempt to develop his ability and expressive tools, so the actors “receive lessonsTraining in this regard requires them to do a lot of continuous and stressful daily exercises.The actor not only had to master the art of speaking, but he also had to master diction, chanting and singing.accompanied by music” (2).